AB0318 CHARACTERISTICS OF PATIENTS WITH RHEUMATOID ARTHRITIS WHO HAVE WITHDRAWN THE LAST BIOLOGICAL DRUG: REAL-LIFE RESULTS FROM A LOCAL REGISTRY. (2nd June 2020) - Rosas, J.; Pons, A.; Senabre Gallego, J. M.; Santos Soler, G.; Bernal, J. A.; García-Gómez, J. A.; Cano, C.; Ivars, E.; Lorente Betoret, M.; Barber, X.
Abstract : Objectives: To assess the characteristics of patients with rheumatoid arthritis (RA), who have withdrawn the last biological drug (bDMARD), and to know the reasons for withdrawal of treatment. Methods: Retrospective and cross-sectional study on December 31, 2019, of patients with RA, treated with any of the bDMARDs, including JAK (JAKi) inhibitor drugs, commonly used, from 1/1/2000 to 12/31/2019. General data were collected from patients, and RA: time of evolution, presence of rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA), type of bDMARD, time in bDMARD, and cause of withdrawal. Results: Of 252 patients, who have received some bDMARD, 81 (32%) patients had withdrawn on 12/31/2019. 62 (77%) patients were women, with a mean age at diagnosis of RA of 48 years (SD: 16.5 years) and 59.5 (15) years at the beginning of the first bDMARD (F1), with an average evolution of RA 10.2 (2.5) years. 68% and 74% of patients were positive for RF and ACPA, respectively. In 64 (79%) patients, bDMARD was withdrawn as second to fifth bDMARD received (F2 to F5): as F2: 37/81 (46%) patients, F3: 14 (18%), F4: 8 (10%) and as F5: (6%) patients. When comparing the last bDMARD received, before the suspension as F1 vs F2-F5, 95% vs. 61% of patients (p <0.0001), the drug was an anti-TNF (TNFi); Abatacept: 1 (1%) vs 9 (14%); Tocilizumab: 0% vs 8 (12%); Rituximab: 1 (1%) vs 5 (8%) and JAKi: 4 (5%) vs 3 (5%). The mean time in treatment with some bDMARD was 2.6 (SD: 3) years in the F1 group vs 1.7 (2) years in the F2-F5 group (p = 0.034). Among the F3-F5 patients, 9 (14%) patients had failed at 2 different previous therapeutic targets and 6 (9%) at 3 targets. No differences were detected between the F1 group vs F2-F5, regarding the causes of withdrawal of bDMARD: whether it had occurred due to 1) loss of efficacy (25/31% patients vs 19/30%); 2) adverse events (31/38% vs. 29/45%): infection: 18/81 (22%) patients, malignancy: 5 (6%), malaise/pain: 11 (14%), laboratory parameters alteration: 7 (9%), death: 5 (6%), others: 14 (17%); 3) change of address/loss of follow-up (20/25% vs. 7/11%) or by 4) voluntary abandonment of treatment by the patient (5/6% vs. 9/14%). Conclusion: 1. 32% of patients with RA withdraw the bDMARD. 2. The group treated with TNFi withdraws it significantly higher among the F1 group. 3. Survival of bDMARD is significantly higher in group F1 compared to F2-F5. 4. No differences were detected between the groups regarding the cause of withdrawal of bDMARD. 25% -30% of patients withdraw it due to loss of follow-up or voluntary abandonment of bDMARD. Acknowledgments: The study was supported by a research grant from the Association for Research in Rheumatology of the Marina Baixa (AIRE-MB). Disclosure of Interests: None declared